A mobile application using IoT enabled navigation system for bus riders - G, Nivedhitha; Carmel Mary Belinda M.J, Dr; G, Nivedhitha (International Journal of Engineering and Technology, 2018)
A bus rider often faces the problem of losing track with the bus timing and position. Towards the goal of making it easy for the student boarding college buses, we make use of the Internet of Things (IoT) technology. It provides the followingservices for the bus users: 1) location and progress information of the required bus 2) tracking nearby buses and3) automatic attendance registration of the bus. With this system, we describe various challenges and a few potentialsolutions such that the bus riders feel more convenience with this integration of Internet of Things (IoT) to transportservices.